A Novel Interactive Virtual Medical Student Clinical Rotation for Ophthalmology - Frisbie, James; Cornman, Hannah; Swamy, Ramya; Alexander, Janet Leath; Kemp, Pavlina S.; Friedrich, Rebekah; Driscoll, Colleen A. Hughes; Levin, Moran R. (Journal of Academic Ophthalmology, 2022)
Objective This article describes a novel clinical rotation that uses technology to create a remote ophthalmology learning experience with the goal of improving virtual exposure to medical and surgical ophthalmic training for medical students.Methods Our unique curriculum incorporates mobile-mounted tablets which allow students to virtually participate in inpatient consults, clinic, and ophthalmic surgery. An adaptable mounting device attached to the slit lamp allows students to observe examinations in real time, enhancing recognition of ocular pathologies. Students participate in a robust curriculum that includes independent learning modules, video lectures, interactive modules, podcasts, and surgical video rounds. Students engage with residents and faculty in interactive-guided lectures and case-based discussions that focus on the American Academy of Ophthalmology white paper teaching objectives. Students are mailed surgical instruments and participate in surgical modules and faculty-led virtual wet laboratories.Results Our unique virtual curriculum combines didactic learning, interactive content, and novel technology applications such as mobile tablets, slit lamp-mounted devices, and faculty-led virtual wet laboratories.Conclusion Virtual technologies can be utilized to enhance ophthalmology medical student education in a safe and effective way during the coronavirus disease 2019 pandemic, and to improve educational access in the future.
Keywords: technology; curriculum; medical student education; surgical curriculum; surgical teaching; ophthalmology rotation; surgical skills